Advanced Analysis of Atmospheric and Terrestrial Solar Barriers via Photovoltaic Systems in Arid Environments : Methodologies and Implications for Solar Energy (London Journal of Research In Science: Natural and Formal, 2025)
This study aims to evaluate atmospheric and terrestrial solar barriers using photovoltaic installations in arid regions. Solar barriers, such as desert aerosols and dust deposits, can significantly affect the performance of photovoltaic systems. The impact of these barriers on solar radiation was analyzed through aerosol optical depth (AOD) and the thickness of dust deposits on solar modules. The results show that solar barriers reduce the amount of solar radiation reaching the photovoltaic cells, thus affecting their performance. The variations in AOD and deposit thickness were measured under different atmospheric conditions, demonstrating a significant correlation with the decrease in global solar radiation. The study utilizes two solar systems installed side by side, one being kept clean and the other left with deposits to simulate the effects of solar barriers. Observations show that simultaneous solar barriers, such as hazy skies and dusty surfaces, have a greater impact than each barrier taken individually. The findings from this research provide valuable insights for optimizing the location and maintenance of solar installations, thereby maximizing their energy efficiency. This study contributes to a better understanding of the effects of solar barriers and proposes mitigation strategies to improve solar radiation capture in arid environments.
Keywords: Aleurodicusrugioperculatus; Aspergillus spp.; host crops and symbiosis; GIS; territorial planning; spatial sampling; urban growth